Pengaruh Work-Life Balance dan Stres Kerja terhadap Kinerja Karyawan PT Cipta Wahana Persada Surabaya - Krido Hary Gunawan; Badriyah Badriyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze in more depth the influence of work-life balance and job stress on employee performance at PT Cipta Wahana Persada Surabaya. The study employed a quantitative method with a survey approach, enabling researchers to obtain objective data based on real-world conditions. The study sample consisted of 38 employees selected through a saturation sampling technique, as the entire population was used as respondents. Data processing was conducted using SPSS version 29.0, with a series of stages including instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing to determine the influence of each variable. The results indicate that work-life balance and job stress simultaneously have a significant effect on employee performance. Partially, work-life balance has been shown to have a positive and significant impact on performance, while job stress also has a significant effect, albeit with a negative effect on productivity. These findings emphasize the importance of maintaining a balance between work and personal life and managing stress effectively to enable employees to perform optimally. Therefore, companies need to pay attention to these two factors to improve organizational performance and productivity.